2017
DOI: 10.1111/1745-5871.12208
|View full text |Cite
|
Sign up to set email alerts
|

Age‐differentiated impact of land appropriation and resettlement on landless farmers: a case study of Xinghua village, China

Abstract: Land appropriation and subsequent resettlement of rural inhabitants are central to urbanisation in China. Often, the result is the impoverishment of landless farmers, who are a principal source of social unrest in the country. In the literature, landless farmers are often wrongly assumed to be a homogeneous group. In contrast, this paper presents the age‐differentiated experiences of land appropriation and resettlement among farmers. Using the case study of Xinghua village in China, and by reference to data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Third, we need a better understanding of the uneven impact of land consolidation on various segments of society [36,37]. Our results show that age is an important factor in determining the life satisfaction of resettlers.…”
Section: Discussionmentioning
confidence: 88%
“…Third, we need a better understanding of the uneven impact of land consolidation on various segments of society [36,37]. Our results show that age is an important factor in determining the life satisfaction of resettlers.…”
Section: Discussionmentioning
confidence: 88%
“…People having positive experiences could lead to positive environmental behaviors [12]. While policymakers and researchers have given great attention to China's landless farmers in terms of employment and livelihood restoration [13][14][15], they have left land expropriation and its emotional impacts relatively under-examined [16]. In attending to this lacuna, this paper aims to unpack the emotional aspects of "land" within the Chinese context.…”
Section: Study Areamentioning
confidence: 99%
“…It has been reported that more than 250-300 million people worldwide have been displaced over the past 20 years [11]. In China, the estimated number is 40 to 50 million and it will reach 110 million by 2030 [12]. Moreover, there is more than 90% illegal land acquisition by local governments in several cities [13], which have caused related legal and land-acquisition and resettlement (LAR) conflicts [13,14].…”
Section: Introductionmentioning
confidence: 99%